1977
DOI: 10.1037/0096-1523.3.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Pitch continuity and speech source attribution.

Abstract: Two experiments showed that continuity of the pitch contour is an important perceptual indicator that a formant pattern comes from a single speech source. Subjects listened to repeatedly played formant patterns that changed smoothly between two vowels. When the pitch was a monotone, these patterns were heard as containing semivowels and liquid consonants; but when a discontinuous, steplike pitch contour was imposed on the patterns, they divided into two perceptually distinct speech sources, and the phonemic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…The tone precursors maintainedacoustic compatibility with the FOof the test word, without having the incompatible formant spacing of some of Diehl et al 's stimuli. The finding of no difference in rate effects induced by the tone precursors and the plain precursors is consistent with the importance that has been attributed to FO and its harmonics in isolating one speaker's voice from many (Darwin & Bethell-Fox, 1977), and ir determining what acoustic energy contributes to phonetic perception Darwin & Gardner, 1986).…”
Section: Discussionsupporting
confidence: 71%
“…The tone precursors maintainedacoustic compatibility with the FOof the test word, without having the incompatible formant spacing of some of Diehl et al 's stimuli. The finding of no difference in rate effects induced by the tone precursors and the plain precursors is consistent with the importance that has been attributed to FO and its harmonics in isolating one speaker's voice from many (Darwin & Bethell-Fox, 1977), and ir determining what acoustic energy contributes to phonetic perception Darwin & Gardner, 1986).…”
Section: Discussionsupporting
confidence: 71%
“…Darwin and Bethell-Fox (1977) showed that, in synthesized speech, a sudden change in fundamental frequency created a boundary across which phonetic interpretation processes would not integrate spectral information. Bregman, Ahad, Kim, and Melnerich (1994) and showed that the suddenness of changes in amplitude affected the tendency of a particular frequency to stand out from a background of other pitches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a formant (frequencies with greater energy that correspond to vowel identity) of a single vowel may become segregated when the formant has a differing F 0 under certain conditions (Broadbent and Ladefoged, 1957;Gardner, Gaskill, and Darwin, 1989). Finally, speech stimuli with discontinuous pitch contours tend to segregate at the discontinuities (Darwin and Bethell-Fox, 1977).…”
Section: Harmonicity and Pitchmentioning
confidence: 99%